Improvement of the elements of chemical protection of spruce trees against spruce bud scales (Hemiptera: Coccidae: Physokermes) in ornamental plants’ arboreta in the Kharkiv Region - Melenti, V. O. (The Kharkiv Entomological Society Gazette, 2019)
Chemical protection of spruce trees against spruce bud scales (spruce bud scale — Physokermes piceae (Schrank, 1801), small spruce bud scale — Physokermes hemicryphus (Dalman, 1826), and Hungarian spruce bud scale — Physkermes inopinatus Danzig et Kozаr, 1973) has been applied in arboreta in the Kharkiv Region for three years. The proposed protection system allows to effectively reduce the abundance of spruce bud scales or entirely relieve trees from them within 2–3 years period. System and complex insecticides with the addition of growth stimulator to the mixture contains were used for protection. Technical efficiency of tested insecticides is 90–97%. The optimal terms of protection have been determined which allows carrying out one treatment per season. 3 tabs, 16 refs.